Peningkatan Jiwa Kepemimpinan Santri Melalui Event Panggung Gembira 633 di Pondok Pesantren Darul Amanah Kendal - Durrotul Hikmah Yuliangsih; Hayu Rizki Permata; Fahrayza Malika Alaika Salamullah; Dayung Ramadhan; Ahmad Ta’rifin (KHIDMAH: Jurnal Pengabdian Masyarakat, 2024)
Panggung Gembira is a grand arts festival consisting of various interesting and valuable performances. The aim of conducting this grand arts festival was by including a very high education aspect, namely developing strong mental and moral qualities, training them to think innovatively and exploring the creativity of male and female students with stunning performances and Islamic nuances. This festival was organized by TMI grade 6 students and assisted by MTS grade 1 to TMI grade 4. The implementation methods for this activity are the preparation method, visit method, and case study. The result of this activity is to form and develop strong moral and mental qualities in students. The students can strongly explore their creativity so that they can form a spirit of Islamic leadership.